2021
DOI: 10.3390/molecules26164876
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations for Effects of Fluoropolymer Binder Content in CL-20/TNT Based Polymer-Bonded Explosives

Abstract: In order to better understand the role of binder content, molecular dynamics (MD) simulations were performed to study the interfacial interactions, sensitivity and mechanical properties of 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane/2,4,6-trinitrotoluene (CL-20/TNT) based polymer-bonded explosives (PBXs) with fluorine rubber F2311. The binding energy between CL-20/TNT co-crystal (1 0 0) surface and F2311, pair correlation function, the maximum bond length of the N–NO2 trigger bond, and the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The binding energy denotes the degree of interaction among the different components and can reflect the thermal stability of the system. 24 A higher binding energy indicates a stronger interaction between the components and therefore a more stable system. It is clearly seen that the E bind value of the compounds gradually decreases with an increase in temperature, which demonstrates that the thermodynamic stability of the system decreases.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding energy denotes the degree of interaction among the different components and can reflect the thermal stability of the system. 24 A higher binding energy indicates a stronger interaction between the components and therefore a more stable system. It is clearly seen that the E bind value of the compounds gradually decreases with an increase in temperature, which demonstrates that the thermodynamic stability of the system decreases.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The binding energy denotes the degree of interaction among the different components and can reflect the thermal stability of the system. 24 A higher binding energy indicates a stronger The corresponding deviations are given in parentheses. interaction between the components and therefore a more stable system.…”
Section: Cohesive Energy Densitymentioning
confidence: 99%
“…Based on the principle of the smallest bond order (PSBO) calculated via quantum chemistry, more sensitive energetic compounds usually contain a smaller bond order of trigger bond in molecules, and it is known that the CL-20 component in TNT/CL-20 decomposes earlier in detonation because CL-20 is more sensitive [ 24 , 53 ]. Therefore, the stability of the N-NO 2 bond in CL-20 as a trigger bond was investigated using the Mayer BOD approach ( Table 2 ) [ 44 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hübner et al characterized a nanoscale HMX/CL-20 cocrystal prepared by spray flash evaporation through tip-enhanced Raman spectroscopy and proposed that the HMX surface finishing might contribute to the impact sensitivity of HMX/CL-20 [ 19 ]. The major part of the theoretical approaches consisted of classical molecular dynamic simulations of intermolecular interactions, vibrational spectra and detonation performance, where the atomic interactions were based on sophisticated force fields [ 20 , 21 , 22 , 23 , 24 ]. All these works demonstrated that energetic cocrystals created a distinct solid-state arrangement at the molecular level and the intermolecular non-covalent interactions were the main driving forces for the cocrystal formation [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the incorporation of fluorine to HTPB-DA, the interfacial interaction of the composite is somewhat decreased, so that the Wa/γmf value of NdFeB-M/HTPB-F3-DA is decreased from 7.11 to 4.69 [39]. Meantime, the spreading coefficient of the system is improved from 21.86 mJ m -2 to 24.21 mJ m -2 .…”
Section: Rheological Studymentioning
confidence: 99%